Adaptor protein 3BP2 regulates dectin-1-mediated cellular signalling to induce cytokine expression and NF-κB activation. Issue 4 (25th February 2022) - Chihara, Kazuyasu; Chihara, Yuri; Takeuchi, Kenji; Sada, Kiyonao
Abstract : The adaptor protein c-Abl Src homology 3 domain-binding protein-2 (3BP2) is phosphorylated by spleen tyrosine kinase (Syk), and the phosphorylation of Tyr 183 is important in the regulation of immune responses. Recently, we reported that 3BP2 plays important roles in phagocytosis and chemokine expression mediated by the Fc receptor for IgG. Although it is well established that various phagocytic cells express Syk-coupled C-type lectin receptors (CLRs) to induce innate immune responses, the functions of 3BP2 and the physiological relevance of the phosphorylation of Tyr 183 remain elusive. In this study, we generated genome-edited mice and observed that 3BP2 influenced the development of bone marrow-derived dendritic cells (BMDCs) induced by granulocyte-macrophage colony-stimulating factor. In addition, we found that 3BP2 was critical for cytokine expression induced by Syk-coupled CLRs — dectin-1 and macrophage-inducible C-type lectin. Immunoblotting analyses revealed that 3BP2 was required for the dectin-1-induced activation of NF-κB p65. The impaired expression of cytokines and activation of NF-κB in 3BP2-mutant cells were restored by wild-type 3BP2, suggesting that 3BP2 was involved in the dectin-1-mediated signalling that led to NF-κB activation. Furthermore, we found that the phosphorylation of Tyr 183 is not essential for cytokine expression and that 3BP2 in combination with caspase recruitment domain family member 9 activates NF-κB in HEK-293T cells. Collectively, these results indicate that in addition to the development of BMDCs, 3BP2 plays an important role in the dectin-1-induced activation of NF-κB and cytokine expression.